Strategi UMKM Rangginang Dalam Pengembangan Produk Pada Era Modern di Masa Pandemi Covid-19: Studi pada UMKM Rangginang “KARYA SEJAHTERA KEDIRI” Cap Mawar Desa Sidomulyo, Kecamatan Wates, Kabupaten Kediri - Yani Dwi Restanti (JUMBA (Jurnal Manajemen, Bisnis, dan Akuntansi), 2023)
This research wants to know how the strategy of UMKM Rangginang Cap Mawar "KARYA SEJAHTERA KEDIRI" in developing rangginang products in the modern era during the covid-19 pandemic using the SWOT analysis method (Strength, Weakness, Opportunity, Threat). The type of research used is Qualitative research using a Descriptive approach. The data used are qualitative and quantitative data with data collection techniques by observation and interview to the owner of UMKM Rangginang Cap Mawar "KARYA SEJAHTERA KEDIRI". The results showed that MSMEs "KARYA SEJAHTERA KEDIRI", during the pandemic experienced a decrease in sales levels, this was due to the less than optimal utilization of social media for marketing and promotional activities, the lack of utilization of social media for marketing. Suggestions that can be made to improve marketing use and improve business development strategies by producing quality rangginang cap roses, adding variations in flavors and shapes of rengginang, variations in packaging and presentation of packaging from small, medium and large sizes, selling at prices that are appropriate for positioning in the market, namely in the lower middle market. Increase sales promotion through social media other than Facebook and Instagram, namely through, Twitter, YouTube and Market Place.